(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Тhe antifungal activity (AFA) of 4 strains of Trametes gibbosa was investigated regarding potentially pathogenic for humans and animals filamentous fungi. AFA was evaluated by using 3 approaches: in mutual growing, using samples of culture liquid (CL) and mycelial extract (ME). In dual culture partial and complete overgrowth reactions on test fungi by T. gibbosa were observed. The CL and ME samples inhibited the growth rate of mycelia of test fungi up to 55.6% and 29.7%, respectively. Thus, the T. gibbosa collections, especially CL samples, possess AFA against studied filamentous fungi and are perspective for further research as a source of antimycotic compounds.